Strikes in Peru: economic and institutional determinants - Yamada, Gustavo; Salgado, Edgar (Universidad del Pacífico, 2005)
The paper illustrates the pro-cyclical behavior of strikes in the Peruvian private sector with the number of strikes rising with economic growth and falling in periods when the economy is in recession. In the first scenario, workers can bargain for higher wage levels without fear of losing their jobs. In the second, the contrary happens. The paper finds that the frequency of strike activity depends on the changes in labor law. lndeed, the drastic changes introduced in the labor legislation in 1992 brought a reduction in the number of strikes in all phases of the economical cycle. An important result is the reduction in the elasticity of the number of strikes as a response to legal changes affecting the labor market. Technically, there is a variation in both coefficients of the estimated regression, intercept and parameter. lf labor reform had not been introduced in 1992, the number of strikes would have increased. The labor reform thus prevented the loss of about 15 million man-hours involving 300.000 workers.